2022
DOI: 10.1186/s13287-022-02742-1
|View full text |Cite
|
Sign up to set email alerts
|

A dual role of HIF1α in regulating osteogenesis–angiogenesis coupling

Abstract: Objectives The hypoxia-inducible factor 1-α (HIF1α), a key molecule in mediating bone-vessel crosstalk, has been considered a promising target for treating osteoporosis caused by gonadal hormones. However, senile osteoporosis, with accumulated senescent cells in aged bone, has a distinct pathogenesis. The study aimed at revealing the unknown role of HIF1α in aged bone, thus broadening its practical application in senile osteoporosis. Materials and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…[22] Additionally, HIF-1 is a crucial molecule that mediates bone-vascular interaction, and up-regulating the HIF-1 signaling pathway can promote angiogenesis and alleviate bone loss in ovariectomized (OVX) mice. [21,23] VEGF is a crucial regulator of angiogenesis that plays a significant role in bone metabolism. [24][25][26] Research has demonstrated that VEGF contributes to the differentiation of mesenchymal stem cells, making them more inclined towards osteogenic differentiation, by regulating the transcription factors RUNX2 and PPARγ2.…”
Section: Discussionmentioning
confidence: 99%
“…[22] Additionally, HIF-1 is a crucial molecule that mediates bone-vascular interaction, and up-regulating the HIF-1 signaling pathway can promote angiogenesis and alleviate bone loss in ovariectomized (OVX) mice. [21,23] VEGF is a crucial regulator of angiogenesis that plays a significant role in bone metabolism. [24][25][26] Research has demonstrated that VEGF contributes to the differentiation of mesenchymal stem cells, making them more inclined towards osteogenic differentiation, by regulating the transcription factors RUNX2 and PPARγ2.…”
Section: Discussionmentioning
confidence: 99%
“…Both HIF‐1α and HIF‐2α are involved in managing prolonged oxidative damage in aging‐ and obesity‐related diseases 67–70 . Particularly, HIF‐1α plays a key role in the stimulation of osteoclast formation in aging‐ and obesity‐induced osteoporosis 70–72 . Consistently, HIF‐2α has been shown to play a role in the development of obesity and exerts anti‐osteogenic actions through upregulating the expression of receptor activator of nuclear factor kappa‐Β ligand (RANKL) that can influence osteoclastogenesis 69,73 .…”
Section: Discussionmentioning
confidence: 99%
“…[67][68][69][70] Particularly, HIF-1α plays a key role in the stimulation of osteoclast formation in agingand obesity-induced osteoporosis. [70][71][72] Consistently, HIF-2α has been shown to play a role in the development of obesity and exerts anti-osteogenic actions through upregulating the expression of receptor activator of nuclear factor kappa-Β ligand (RANKL) that can influence osteoclastogenesis. 69,73 Here, we discovered that HBOT also exerted the hyperoxia-hypoxic paradox in the bone of aging rats, regardless of obesity.…”
Section: Osteoblast Differentiation and Function Markers In Bonementioning
confidence: 98%
“…SIRT3 has been reported to be involved in a variety of aging-related diseases, such as Alzheimer’s disease, Parkinson’s disease, cardiovascular disease, and bone diseases ( 20 , 21 ). A previous study showed that the senescence of bone mesenchymal stem cells (BMSCs) could lead to osteogenic damage and osteoporosis ( 22 ). And the maintenance of mitochondrial NAD + levels and the expression of SIRT3 could delay the senescence of MSCs ( 23 ).…”
Section: Introductionmentioning
confidence: 99%